Особливості кристалографії сльози при рефракційній хірургії методами RеLЕх SMILE та Фемто-LASІK на очах з міопією та міопічним астигматизмом - Завгородня, Наталія Григорівна; Дорошенко, Ю. Ю.; Zavgorodnia, N. H.; Doroshenko, Yu. Yu. (My University, 2024)
Мета. Підвищення якості хірургічного лікування міопії та міопічного астигматизму шляхом уточнення показань до вибору методу корекції на основі кристалографії сльози (СР). Violation of the tear and development of dry eye syndrome is the most frequent problem in refractive surgery. Therefore, careful selection of patients, preoperative evaluation and prevention of the development of diseases of the ocular surface are important to ensure successful results of refractive interventions. The results of surgical treatment of 30 patients (60 eyes) with mild and moderate myopia and myopic astigmatism, who underwent vision correction using the ReLEx SMILE and Femto-LASIK methods, were analyzed. The analysis of tear crystallography indicates a more gentle effect of the ReLEX SMILE technology than Femto-LASIK on the surface of the eye during refractive surgery, which may be related to the preservation of corneal innervation in the absence of corneal valve formation.
Peculiarities of tear crystallography during refractive surgery using ReLEx SMILE and Femto-LASIK methods in eyes with myopia and myopic astigmatism